Exigências de energia em bezerros lactentes F1 holandês x Gir, utilizando a respirometria - Juliana Savia da Silva (2016)
This study aimed to evaluate the influence of three milk supply strategies and ad libitum concentrate on intake, digestibility, nitrogen balance, performance, metabolic profile and behavior, and determine the net energy milk, energy partition and nutritional energyrequirements in dairy calves F1 Holandês x Gir (n = 19) at 30 and 60 days old. The experimental design adopted was completely randomized. The results were analyzed using the GLM procedure of SAS version 9.0 and is considered fixed effects the quantity of milk supplied daily to calves (4, 6 and 8 L/day reconstituted whole milk powder /day). The lineareffect of the variables was analyzed by orthogonal contrasts, being considered significant when 0.05. The digestibility were always above 90% due through extensive involvement of milk in the diet and its highly digestible constituents. At 30 days of age, the provision of 8 L/day milk was most economically efficient because it allowed a greater weight gain with concomitant lower cost of the diet. The quantities of milk influenced the creatinine, cholesterol and glucose concentrations. At 60 days of age, animals receiving lower volume of milk tended to consume more concentrated to compensate for energy deficiency. The supplyof concentrate was significant for the calves that received 4 L/day of milk presented the Lowest cost / kg GMD. Animals that consumed greater quantities of milk and had access to concentrate at will excreted less N fecal. The supply of milk and concentrated influenced theconcentrations of AST and glucose calves. The provision of concentrate promoted prolonged periods of feeding. The demand of liquid energy for maintenance of suckling calves F1 Holandês x Gir, 30 days old, is 73,71 kcal/kgPV0,75, and metabolizable energy for maintenance is 109,44 kcal/kg PV0,75. The energy values of milk are: 4,07 McalElm/kg of MSand 2,67 McalELg/kg of MS